Cordales o muelas del juicio en la Romania Lateral. Un legado cultural greco-latino - Sánchez Corrales, Víctor Manuel (2012)
Based on the theoretical contributions of cognitive linguistics, historical aspects of Hispania and Dacia as roman provinces, and the resulting acculturation of native inhabitants, this article analyzes the neo-Latin dialect lexical creation of the pluriverbal unit dentes ocularii in two languages of Lateral Romania: Spanish and Romanian.